Analisis Kebijakan Pemerintahan Daerah Jawa Timur Tentang Pengembangan SMK Mini di Pondok Pesantren - Maskuri Maskuri; Minhaji Minhaji (Jurnal Pendidikan Islam Indonesia, 2017)
Islamic education in the form of boarding school, in accordance with that nature will make efforts to improve and change the condition. As an oldest educational institution in Indonesia, boarding schools get serious attention from various circles, both public and private. Currently, Islamic boarding schools in Indonesia are not putting science knowledge separated into small part. However, the leaders and managers of boarding school have unified ' science knowledge ' as an integral part of the boarding school. East Java as the province with the second largest number of boarding schools after West Java has proved itself by producing educational policies that favor the development of boarding school. Local regulation Number 9, 2014 on the Implementation of Education became the legal basis for the implementation of Mini Vocational High School (SMK Mini) development program. That is the basic idea actually appeared from the East Java Governor to respond to global competition in the business world. Education policy as a public policy necessarily born out from the political process in East Java, which involve policy actors. In the implementation phase received tremendous attention. That's will be analyze by researcher with public policy approaches, systems theory, power, and Hegelian dialectics.